2005
DOI: 10.1111/j.1600-6143.2005.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Tacrolimus and Cyclosporine in Liver Transplantation: Effects on Renal Function and Cardiovascular Risk Status

Abstract: A retrospective chart review of 1065 consecutive liver allograft recipients in 11 centers from January 1997 to September 1998 was performed. Patients were followed for 3 years or until graft loss. Patients received either tacrolimus (n = 594), cyclosporine (n = 450) or no calcineurin inhibitor (n = 21). Model for end-stage liver disease (MELD) scores at time of transplant were similar between the two groups. During follow-up, more patients switched from cyclosporine to tacrolimus (26.7%) than from tacrolimus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 29 publications
4
42
0
2
Order By: Relevance
“…Besides, several comparative and conversion studies that were performed in kidney transplantation demonstrated that renal function may be better under tacrolimus treatment (5,7). This also was observed in studies on other solid-organ recipients (9) and even in healthy volunteers (10), suggesting that nephrotoxicity may be lower with tacrolimus. On the contrary, posttransplantation diabetes (PTD) may be considered the Achilles' tendon of tacrolimus with a greater incidence with tacrolimus than with CsA (11,12).…”
mentioning
confidence: 62%
“…Besides, several comparative and conversion studies that were performed in kidney transplantation demonstrated that renal function may be better under tacrolimus treatment (5,7). This also was observed in studies on other solid-organ recipients (9) and even in healthy volunteers (10), suggesting that nephrotoxicity may be lower with tacrolimus. On the contrary, posttransplantation diabetes (PTD) may be considered the Achilles' tendon of tacrolimus with a greater incidence with tacrolimus than with CsA (11,12).…”
mentioning
confidence: 62%
“…Tacrolimus has been shown to be less nephrotoxic than cyclosporine. 8,20,21 Although we do not have data on the type of calcineurin inhibitor used following transplant to examine trends in usage over time, cyclo- kidney disease. Third, the median follow-up time of our cohort was relatively short at 2 years, as 25% of transplant recipients did not have serum creatinine values recorded in the registry beyond the year of lung transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Women can have "normal" serum creatinine values despite depressed renal function, because of lower muscle mass compared with males. 21 Missed diagnoses of renal impairment or renal dysfunction in women can lead to inappropriate dosing of nephrotoxic immunosuppressive agents and antibiotics, thus leading to further renal damage. Furthermore, women have reduced nephron mass relative to men and therefore might be more vulnerable to the nephrotoxic effects of calcineurin inhibitors.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Moreover, the fibrogenic potential of tacrolimus also appears to be lower (210), although these results could not be confirmed in a more recent study (135). In nonrenal solid organ transplantation, there are singleand multicenter studies as well as registry analyses demonstrating the benefit of tacrolimus over cyclosporine with regard to renal function (24, [211][212][213][214], although other studies did not observe this benefit of tacrolimus over cyclosporine (215).…”
Section: Comparison Between Cyclosporine and Tacrolimusmentioning
confidence: 99%